Peningkatan Sumber Daya Manusia Pertahanan di Era Volatil, Uncertain, Complex dan Ambiguous - Sadono (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2024)
The development of technology 4.0 gave birth to VUCA (Volatility, Uncertainty, Complexity, and Ambiguity), has a very significant impact on the existence of defense human resources of the Ministry of Defense. This condition affects the performance of Ministry of Defense employees. The data in this paper are collected through reference studies and data analysis from various materials related to human resource development in the VUCA era, such as books, journals, and websites, then examined and analyzed descriptively. The results of the analysis show that in building human resources within the Ministry of Defense, the following are emphasized: 1. Increased Cooperation. The need for cooperation between institutions, institutions and private and universities to collaborate in improving human resources in the defense sector. 2. Empowerment of Training. The need for the development of defense human resources in the VUCA era through IT and communication training. 3. Continuous Evaluation. The importance of implementing evaluations to measure the achievement of IT and communication-based HR development improvements on individual and organizational performance. 4. Strengthening Innovation Culture. The need to build an innovative work environment in facing the VUCA era.